Kolaborasi Inovasi Pelayanan Kesehatan Melalui Mobile Jkn Di Rumah Sakit Siti Khodijah - Trianggraini, Sela Ajeng; Wahyuni, Sri (Institut Riset dan Pengembangan Indonesia, 2024)
Access and quality of health services in Indonesia is still a challenge. Siti Khodijah Hospital collaborates with BPJS Health and the community to develop Mobile JKN innovation. This article aims to examine the innovative collaboration between Siti Khodijah Hospital and BPJS Health in implementing Mobile JKN, as well as its impact on patients and medical staff. This article discusses this collaboration using Pasuraman's public service theory. Collaborative health service innovation through Mobile JKN at Siti Khodijah Hospital has shown positive results and is in line with the Pasuraman public service theory. This innovation has improved access and quality of health services for the community, as well as increased patient satisfaction. This innovation can be an example for other hospitals in Indonesia to develop ICT-based health service innovations.